Efficacy of Prolonged-release Tacrolimus After Conversion From Immediate-release Tacrolimus in Kidney Transplantation: A Retrospective Analysis of Long-term Outcomes From the ADMIRAD Study. Issue 4 (15th March 2023) - Kuypers, Dirk; Weekers, Laurent; Blogg, Martin; Anaokar, Swapneel; del Pilar Repetur, Carola; De Meyer, Vicky; Kanaan, Nada
Abstract : Background: Prolonged-release tacrolimus (PRT) may offer improved outcomes after kidney transplantation compared with immediate-release tacrolimus (IRT). However, data on outcomes beyond 5-y posttransplantation are lacking. Methods: A retrospective, noninterventional chart review study examined long-term graft survival in adult kidney transplant participants in the Adherence Measurement in Stable Renal Transplant Patients Following Conversion From Prograf to Advagraf (ADMIRAD) clinical trial at 4 Belgian sites. Patients were randomized to receive once-daily PRT or twice-daily IRT for 6 mo, followed by treatment as per real-world clinical practice. Data were collected retrospectively from randomization day until December 31, 2018. Primary endpoints included efficacy failure, defined as a composite endpoint of graft loss, biopsy-confirmed acute rejection, and graft dysfunction. Secondary endpoints included overall patient survival and course of kidney function. Results: This analysis included 78.5% of patients from ADMIRAD (n = 108 PRT; n = 64 IRT). The Kaplan–Meier survival rate without efficacy failure from randomization to year 5 was 0.741 (95% confidence interval [CI]: 0.647, 0.813) for the PRT group (n = 80), and 0.667 (95% CI: 0.536, 0.768) for the IRT group (n = 42) and remained higher for PRT throughout 10 y follow-up ( P = 0.041). The Kaplan–Meier estimate of overall survival from the time of last transplant was 0.981 (95% CI: 0.928, 0.995) and 0.880 (95% CI: 0.802, 0.928) at 5 and 10 y in the PRT group. Kidney function parameters and tacrolimus trough levels remained stable over the follow-up period. Conclusions: Patients in the ADMIRAD study who received PRT for up to 10 y had improved long-term outcomes compared with patients receiving IRT, with a consistent effect on both graft and patient survival. Abstract :